Desert sand hybrid fiber cement-based composite material 28d strength prediction method

By fitting the relationship between compressive strength and maintenance days and combining fiber influence factors, a rapid and accurate prediction of the compressive strength of desert sand mixed fiber cement-based composite material in 28 days is achieved, and the cumbersome detection and inaccurate prediction in the existing technology are solved. Problem, shortening the inspection cycle and guiding material adjustment.

CN119309919APending Publication Date: 2025-01-14CHINA RAILWAY 15TH BUREAU GROUP CORPORATION LIMITED +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411484941.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, the 28-day compressive strength prediction method for desert sand mixed fiber cement-based composite materials lacks fast and accurate methods. The traditional detection methods are cumbersome and costly, and the relevant models are mainly focused on the strength prediction of ordinary concrete, which lacks targeting. A fast prediction method for desert sand mixed fiber cement matrix composites.

Method used

By preparing desert sand mixed fiber cement matrix composite specimens, curing and compressive strength test, fitting to obtain a functional expression between compressive strength and maintenance days, considering the influencing factors of fiber type and relative doping, The fitting formula was made to predict the compressive strength of 28 days.

Benefits of technology

It has achieved rapid and accurate prediction of the compressive strength of desert sand mixed fiber cement-based composite materials in 28 days, shortened the detection cycle, and predicted in advance whether the material meets the specified requirements, and guided the adjustment of the mix ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119309919A_ABST
    Figure CN119309919A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of compressive strength prediction of desert sand hybrid fiber cement-based composite materials, in particular to a 28d strength prediction method of a desert sand hybrid fiber cement-based composite material, which comprises the following steps: performing formula fitting on compressive strength at different ages; the function expression between the compressive strength and the number of maintenance days is # imgabs0 #, T is the number of maintenance days, and sigma c is the compressive strength of the corresponding age; a < lambda > and b < lambda > are regression coefficients considering the influence of fiber types and relative mixing amounts, the influence of fiber influence factors on a < lambda > and b < lambda > is considered, a fitting formula of sigma < c > about the fiber influence factor < lambda > and the curing age T is obtained, and lambda and T = 28 are substituted into a prediction formula # imgabs1 #, so that the 28d compressive strength of the desert sand hybrid fiber cement-based composite material can be determined. The prediction method is feasible and effective, and can accurately and quickly predict the 28d compressive strength of the desert sand hybrid fiber cement-based composite material, so that the detection period is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of compressive strength prediction of cement-based engineering composite materials, and in particular to a method for predicting the 28d strength of a desert sand mixed fiber cement-based composite material. Background Art

[0002] Cement-based engineering materials are composite materials with superior deformation performance and good toughness developed in the past decade. They are widely used in bridge deck paving, building structure earthquake resistance and other fields. In high-stress soft rock tunnel projects, ordinary sprayed concrete with poor deformation performance is used for initial support of tunnels, which is difficult to adapt to large deformation of soft rock tunnels, often resulting in cracking and falling of sprayed concrete support. If this cement-based engineering composite material is used for the initial support spray layer of the tunnel, the advantages of this material can be fully utilized. In the actual construction of engineering projects, in order to ensure the safety of construction and operation, a large number of tests are often required to ensure that the performance of cement-based engineering composite materials meets the requirements of the project and specifications. Among them, the compressive strength test is usually carried out 28 days after pouring the cement-based engineering composite material. The 28-day waiting period required for such tests may delay the construction progress, but ignoring the test may cause serious quality problems and may cause serious collapse accidents. Therefore, the rapid and accurate prediction of the 28d compressive strength of concrete is the key to design or quality control.

[0003] Due to the scarcity of river sand resources, if the fine river sand in cement-based engineering composites can be replaced by desert sand, it can not only achieve waste utilization, but also significantly reduce material costs. There is a huge difference in the particle grading between desert sand and river sand. The growth law of the compressive strength of cement-based engineering composites that use desert sand instead of river sand and add mixed fibers will inevitably be affected by the characteristics of desert sand and the fiber type and relative dosage. Therefore, in the 28d strength prediction of desert sand mixed fiber cement-based composites, the fiber influence factor is introduced to consider the influence of fiber type and relative dosage.

[0004] In the related technology, the traditional strength detection method generally detects the strength value by manually operating the testing machine and other equipment. The operation steps are cumbersome, the cost is high and the efficiency is low. In addition, the related strength prediction model focuses on predicting the strength value of ordinary concrete. There is a lack of rapid prediction methods for the strength of desert sand mixed fiber cement-based composite materials. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a method for predicting the 28d strength of desert sand hybrid fiber cement-based composite materials. The present invention obtains a functional expression between the compressive strength and the curing days considering the fiber influence factor λ, and predicts the 28d strength of desert sand hybrid fiber cement-based composite materials through this relationship. The results show that the rapid prediction method is feasible and effective, and can accurately and quickly predict the 28d strength of desert sand hybrid fiber cement-based composite materials, helping to shorten the detection cycle.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0008] Preparation of desert sand hybrid fiber cement-based composite specimens;

[0009] The desert sand mixed fiber cement-based composite material specimens were cured, and the compressive strength of the cured specimens was tested to obtain the compressive strength at different ages;

[0010] The compressive strength curves of different ages were fitted by considering the fiber type and relative dosage to obtain a function expression between the compressive strength and the curing days, which is: Among them, T is the number of maintenance days, σ c is the compressive strength at the corresponding age, a λ , b λ is the regression coefficient considering the influence of fiber type and relative dosage, both of which are functions of fiber influence factor λ. By data fitting, we can get: λ =33814λ 2 -8147.7λ+552.78, b λ =13504λ 2 -3044.2λ+177.49, then the fitting formula of the compressive strength of desert sand hybrid fiber cement-based composites considering the fiber influence factor λ is: By substituting λ (determined according to the incorporated fiber parameters) and T=28 into the fitting formula, its 28-day compressive strength can be predicted.

[0011] In a preferred embodiment of the present invention, the desert sand mixed fiber cement-based composite material includes the following raw materials in parts by weight: 480 to 520 parts of cement, 730 to 770 parts of fly ash, 430 to 460 parts of desert sand, 320 to 330 parts of water, 9.0 to 9.4 parts of water reducer, 13 to 19.5 parts of polyvinyl alcohol fiber, 4.85 to 9.7 parts of polyethylene fiber, and 0.5 part of thickener.

[0012] In a preferred embodiment of the present invention, aλ =62.637~66.41447, b λ =5.93775~6.11714, λ=0.106~0.116.

[0013] In a preferred embodiment of the present invention, the curing days are 3 to 14 days, and the curing temperature is 18° to 22°.

[0014] In a preferred embodiment of the present invention, the curing days are selected from at least 2 days from the 3rd day to the 14th day.

[0015] In a preferred embodiment of the present invention, the curing days are selected from the 3rd day, the 7th day and the 14th day.

[0016] In a preferred embodiment of the present invention, the error value is less than 5%, which meets engineering requirements.

[0017] In a preferred embodiment of the present invention, the water reducer is a high-efficiency polycarboxylate water reducer and water in a weight ratio of 1:3.

[0018] In a preferred embodiment of the present invention, the thickener is hydroxypropyl methylcellulose ether.

[0019] In a preferred embodiment of the present invention, the desert sand has a mud content of 0.64% and a particle size range of 74 μm to 600 μm.

[0020] In a preferred embodiment of the present invention, the method for preparing the desert sand hybrid fiber cement-based composite material specimen comprises the following steps:

[0021] Weigh the following raw materials in parts by weight: 480-520 parts of cement, 730-770 parts of fly ash, 430-460 parts of desert sand, 320-330 parts of water, 9.0-9.4 parts of water reducing agent, 13-19.5 parts of polyvinyl alcohol fiber, 4.85-9.7 parts of polyethylene fiber, and 0.5 parts of thickener;

[0022] Mixing 2 / 3 of desert sand, cement and fly ash with water to obtain a first mixture;

[0023] Adding the remaining 1 / 3 of desert sand, cement and fly ash to the first mixture, and simultaneously adding a water reducing agent, to obtain a second mixture;

[0024] Subsequently, a thickener is added to the second mixture, and the mixture is stirred. Finally, polyvinyl alcohol fibers and polyethylene fibers are added and stirred to obtain a desert sand hybrid fiber cement-based composite material.

[0025] In a preferred embodiment of the present invention, the desert sand mixed fiber cement-based composite material is cast and then cured, and the casting size is a cube of 70.7 mm×70.7 mm×70.7 mm.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The method for predicting the 28d strength of the desert sand hybrid fiber cement-based composite material of the present invention is feasible and effective, and can accurately and quickly predict the 28d strength of the desert sand hybrid fiber cement-based composite material, helping to shorten the detection cycle.

[0028] 2. The present invention can quickly predict the compressive strength of the corresponding desert sand mixed fiber cement-based composite material through the mix ratio of the desert sand mixed fiber cement-based composite material, and can predict in advance whether the desert sand mixed fiber cement-based composite material can meet the relevant requirements, and then correspondingly guide the adjustment of the mix ratio of the desert sand mixed fiber cement-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a fitting curve relationship diagram of the change in compressive strength with age in Example 1 of the present invention, PVA:PE=1.5%:0.5%, 1.5% represents the volume ratio of the PVA fiber volume in the desert sand mixed fiber cement-based composite material, 0.5% represents the volume ratio of the PE fiber volume in the desert sand mixed fiber cement-based composite material, and the volume of the PVA fiber and the PE fiber accounts for 2% of the total volume.

[0030] Figure 2 This is a fitting curve relationship diagram of the change in compressive strength with age in Example 2 of the present invention, PVA:PE=1.25%:0.75%, 1.25% represents the volume ratio of the PVA fiber volume in the desert sand mixed fiber cement-based composite material, 0.75% represents the volume ratio of the PE fiber volume in the desert sand mixed fiber cement-based composite material, and the volume of the PVA fiber and the PE fiber accounts for 2% of the total volume.

[0031] Figure 3 This is a fitting curve relationship diagram of the change in compressive strength with age in Example 3 of the present invention, PVA:PE=1%:1%, 1% represents the volume ratio of PVA fiber in the desert sand mixed fiber cement-based composite material, 1% represents the volume ratio of PE fiber in the desert sand mixed fiber cement-based composite material, and the volume of PVA fiber and PE fiber accounts for 2% of the total volume.

[0032] Figure 4 is the fiber correction factor a λ Relationship curve with fiber influence factor λ.

[0033] Figure 5 is the fiber correction factor b λ Relationship curve with fiber influence factor λ. DETAILED DESCRIPTION

[0034] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0036] Example 1

[0037] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0038] (1) Weigh the following raw materials in parts by weight: 500 parts of cement, 750 parts of fly ash, 445 parts of desert sand, 325 parts of water, 9.2 parts of water reducing agent, 19.5 parts of polyvinyl alcohol fiber (PVA for short), 4.85 parts of polyethylene fiber (PE for short), and 0.5 parts of hydroxypropyl methylcellulose ether.

[0039] (2) Pour 2 / 3 of desert sand, cement and fly ash into a JJ-5 mixing drum, stir for 30 seconds, then add all the water and stir for another 30 seconds to obtain a first mixture.

[0040] (3) The remaining 1 / 3 of desert sand, cement and fly ash are mixed evenly in a feeding basin and then slowly added to the first mixture obtained in step (2). During this period, a water reducing agent is continuously added. The whole process takes about 2 minutes to obtain a second mixture.

[0041] (4) Add hydroxypropyl methylcellulose ether to the second mixture and stir for 30 seconds. Finally, slowly add PVA and PE fibers and disperse them. The whole process takes about 5 minutes. After the fibers are added, switch to high-speed rotation for 2.5 minutes to obtain a desert sand mixed fiber cement-based composite material.

[0042] (5) The desert sand mixed fiber cement-based composite material is cast in a corresponding mold, the size of the uniaxial compressive test piece is 70.7 mm×70.7 mm×70.7 mm, vibrated and covered with plastic wrap, and demolded after 24 hours and placed in a standard curing box for curing to obtain desert sand mixed fiber cement-based composite materials of different ages. The compressive strength of the cured desert sand mixed fiber cement-based composite material is tested to obtain the compressive strength of different ages.

[0043] Example 2

[0044] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0045] (1) Weigh the following raw materials in parts by weight: 500 parts of cement, 750 parts of fly ash, 445 parts of desert sand, 325 parts of water, 9.2 parts of water reducing agent, 16.25 parts of PVA, 7.28 parts of PE, and 0.5 parts of hydroxypropyl methylcellulose ether.

[0046] (2) Pour 2 / 3 of desert sand, cement and fly ash into a JJ-5 mixing drum, stir for 30 seconds, then add all the water and stir for another 30 seconds to obtain a first mixture.

[0047] (3) The remaining 1 / 3 of desert sand, cement and fly ash are mixed evenly in a feeding basin and then slowly added to the first mixture obtained in step (2). During this period, a water reducing agent is continuously added. The whole process takes about 2 minutes to obtain a second mixture.

[0048] (4) Add hydroxypropyl methylcellulose ether to the second mixture and stir for 30 seconds. Finally, slowly add PVA and PE fibers and disperse them. The whole process takes about 5 minutes. After the fibers are added, switch to high-speed rotation for 2.5 minutes to obtain a desert sand mixed fiber cement-based composite material.

[0049] (5) The desert sand mixed fiber cement-based composite material is cast in a corresponding mold, the size of the uniaxial compressive test piece is 70.7 mm×70.7 mm×70.7 mm, vibrated and covered with plastic wrap, and demolded after 24 hours and placed in a curing box for curing to obtain desert sand mixed fiber cement-based composite materials of different ages. The compressive strength of the desert sand mixed fiber cement-based composite materials after curing is tested to obtain the compressive strength of different ages.

[0050] Example 3

[0051] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0052] (1) Weigh the following raw materials in parts by weight: 500 parts of cement, 750 parts of fly ash, 445 parts of desert sand, 325 parts of water, 9.2 parts of water reducing agent, 13 parts of PVA, 9.7 parts of PE, and 0.5 parts of hydroxypropyl methylcellulose ether.

[0053] (2) Pour 2 / 3 of desert sand, cement and fly ash into a JJ-5 mixing drum, stir for 30 seconds, then add all the water and stir for another 30 seconds to obtain a first mixture.

[0054] (3) The remaining 1 / 3 of desert sand, cement and fly ash are mixed evenly in a feeding basin and then slowly added to the first mixture obtained in step (2). During this period, a water reducing agent is continuously added. The whole process takes about 2 minutes to obtain a second mixture.

[0055] (4) Add hydroxypropyl methylcellulose ether to the second mixture and stir for 30 seconds. Finally, slowly add PVA and PE fibers and disperse them. The whole process takes about 5 minutes. After the fibers are added, switch to high-speed rotation for 2.5 minutes to obtain a desert sand mixed fiber cement-based composite material.

[0056] (5) The desert sand mixed fiber cement-based composite material is cast in a corresponding mold, the size of the uniaxial compressive test piece is 70.7 mm×70.7 mm×70.7 mm, vibrated and covered with plastic wrap, and demolded after 24 hours and placed in a standard curing box for curing to obtain desert sand mixed fiber cement-based composite materials of different ages. The compressive strength of the cured desert sand mixed fiber cement-based composite material is tested to obtain the compressive strength of different ages.

[0057] Example 4

[0058] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0059] (1) Weigh the following raw materials in parts by weight: 500 parts of cement, 750 parts of fly ash, 445 parts of desert sand, 325 parts of water, 9.2 parts of water reducing agent, 9.75 parts of PVA, 12.13 parts of PE, and 0.5 parts of hydroxypropyl methylcellulose ether.

[0060] (2) Pour 2 / 3 of desert sand, cement and fly ash into a JJ-5 mixing drum, stir for 30 seconds, then add all the water and stir for another 30 seconds to obtain a first mixture.

[0061] (3) The remaining 1 / 3 of desert sand, cement and fly ash are mixed evenly in a feeding basin and then slowly added to the first mixture obtained in step (2). During this period, a water reducing agent is continuously added. The whole process takes about 2 minutes to obtain a second mixture.

[0062] (4) Add hydroxypropyl methylcellulose ether to the second mixture and stir for 30 seconds. Finally, slowly add PVA and PE fibers and disperse them. The whole process takes about 5 minutes. After the fibers are added, switch to high-speed rotation for 2.5 minutes to obtain a desert sand mixed fiber cement-based composite material.

[0063] (5) The desert sand mixed fiber cement-based composite material is cast in a corresponding mold, the size of the uniaxial compressive test piece is 70.7 mm×70.7 mm×70.7 mm, vibrated and covered with plastic wrap, and demolded after 24 hours and placed in a standard curing box for curing to obtain desert sand mixed fiber cement-based composite materials of different ages. The compressive strength of the cured desert sand mixed fiber cement-based composite material is tested to obtain the compressive strength of different ages.

[0064] Example 5

[0065] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0066] (1) Weigh the following raw materials in parts by weight: 480 parts of cement, 730 parts of fly ash, 430 parts of desert sand, 320 parts of water, 9.0 parts of water reducing agent, 19.5 parts of polyvinyl alcohol fiber (PVA for short), 4.85 parts of polyethylene fiber (PE for short), and 0.5 parts of hydroxypropyl methylcellulose ether.

[0067] (2) Pour 2 / 3 of desert sand, cement and fly ash into a JJ-5 mixing drum, stir for 30 seconds, then add all the water and stir for another 30 seconds to obtain a first mixture.

[0068] (3) The remaining 1 / 3 of desert sand, cement and fly ash are mixed evenly in a feeding basin and then slowly added to the first mixture obtained in step (2). During this period, a water reducing agent is continuously added. The whole process takes about 2 minutes to obtain a second mixture.

[0069] (4) Add hydroxypropyl methylcellulose ether to the second mixture and stir for 30 seconds. Finally, slowly add PVA and PE fibers and disperse them. The whole process takes about 5 minutes. After the fibers are added, switch to high-speed rotation for 2 minutes to obtain a desert sand mixed fiber cement-based composite material.

[0070] (5) The desert sand mixed fiber cement-based composite material is cast in a corresponding mold, the size of the uniaxial compressive test piece is 70.7 mm×70.7 mm×70.7 mm, vibrated and covered with plastic wrap, and demolded after 24 hours and placed in a standard curing box for curing to obtain desert sand mixed fiber cement-based composite materials of different ages. The compressive strength of the cured desert sand mixed fiber cement-based composite material is tested to obtain the compressive strength of different ages.

[0071] Example 6

[0072] A method for predicting the 28d strength of a desert sand hybrid fiber cement-based composite material comprises the following steps:

[0073] (1) Weigh the following raw materials in parts by weight: 520 parts of cement, 770 parts of fly ash, 460 parts of desert sand, 330 parts of water, 9.4 parts of water reducing agent, 19.5 parts of polyvinyl alcohol fiber (PVA for short), 4.85 parts of polyethylene fiber (PE for short), and 0.5 parts of hydroxypropyl methylcellulose ether.

[0074] (2) Pour 2 / 3 of desert sand, cement and fly ash into a JJ-5 mixing drum, stir for 30 seconds, then add all the water and stir for another 30 seconds to obtain a first mixture.

[0075] (3) The remaining 1 / 3 of desert sand, cement and fly ash are mixed evenly in a feeding basin and then slowly added to the first mixture obtained in step (2). During this period, a water reducing agent is continuously added. The whole process takes about 2 minutes to obtain a second mixture.

[0076] (4) Add hydroxypropyl methylcellulose ether to the second mixture and stir for 30 seconds. Finally, slowly add PVA and PE fibers and disperse them. The whole process takes about 5 minutes. After the fibers are added, switch to high-speed rotation for 3 minutes to obtain a desert sand mixed fiber cement-based composite material.

[0077] (5) The desert sand mixed fiber cement-based composite material is cast in a corresponding mold, the size of the uniaxial compressive test piece is 70.7 mm×70.7 mm×70.7 mm, vibrated and covered with plastic wrap, and demolded after 24 hours and placed in a standard curing box for curing to obtain desert sand mixed fiber cement-based composite materials of different ages. The compressive strength of the cured desert sand mixed fiber cement-based composite material is tested to obtain the compressive strength of different ages.

[0078] Results Analysis

[0079] Table 1 Raw material composition information table of Examples 1 to 3, unit: mass parts

[0080] serial number cement Fly ash sand water Water reducing agent PVA PE Thickener Example 1 500 750 445 325 9.2 19.5 4.85 0.5 Example 2 500 750 445 325 9.2 16.25 7.28 0.5 Example 3 500 750 445 325 9.2 13 9.7 0.5

[0081] Table 1 is a raw material composition information table of Examples 1 to 3, wherein the mud content of the desert sand is 0.64% and the particle size distribution is 74 μm to 600 μm.

[0082] Table 2 Actual measured values ​​of compressive strength of Example 1 to Example 3 at 3 to 28 days

[0083] serial number 3d / MPa 7d / MPa 14d / MPa 28d / MPa Example 1 22.42 32.44 42.38 52.58 Example 2 22.69 33.29 45.92 53.10 Example 3 23.47 33.82 46.07 55.04

[0084] Table 3 Predicted compressive strength values ​​for 3 to 28 days in Example 1 to Example 3

[0085] serial number 3d / MPa 7d / MPa 14d / MPa 28d / MPa Example 1 21.3 33.53 43.68 51.47 Example 2 21.61 34.84 45.21 53.12 Example 3 22.36 35.44 46.22 54.51

[0086] Table 4 Compressive strength error value of Example 1 to Example 3 / %

[0087]

[0088]

[0089] Table 2 shows the actual measured values ​​of compressive strength of Examples 1 to 3 after 3 to 28 days, Table 3 shows the predicted values ​​of compressive strength of Examples 1 to 3 after 3 to 28 days, and Table 4 shows the error values ​​of compressive strength of Examples 1 to 3 (%) Figure 1 to Figure 3 They are the fitting curve relationship diagrams of Examples 1 to 3 respectively. After calculation, it is found that the fitting formula of Example 1 is Middle λ =62.637, b λ =6.0767, R 2 =0.9861, a in the fitting formula of Example 2 λ =64.3898, b λ =5.9378, R 2 =0.9926, a in the fitting formula of Example 3 λ =66.4145, b λ =6.1171, R 2 =0.9855. It can be seen that when the function is fitted, the goodness of fit is above 0.9855, the maximum error between the predicted intensity value and the actual intensity value is 4.99%, and the prediction accuracy of the 28-day intensity is even smaller, with an average error of only 1.04%, indicating that the 28-day intensity prediction accuracy is good.

[0090] From the fitting curves of Examples 1 to 3, the values ​​of the correction coefficients a and b considering the fiber type and relative dosage are obtained, as shown in Table 5. The physical and mechanical properties of PVA and PE fibers are shown in Table 6.

[0091] Table 5 Correction coefficient a considering fiber type and relative dosage λ , b λ The result of the value

[0092] serial number <![CDATA[a λ ]]> <![CDATA[b λ ]]> Example 1 62.637 6.07668 Example 2 64.38979 5.93775 Example 3 66.41447 6.11714

[0093] Table 6 Physical and mechanical properties of PVA and PE fibers

[0094]

[0095] The fiber influence factor λ is introduced to describe the influence of different fiber types and fiber relative volume content on the 28d strength prediction of desert sand hybrid fiber cement-based composites. The expression of fiber influence factor λ is:

[0096]

[0097] Where: V a and V e are the volume content of PVA and PE fibers respectively; L a / d a and L e / d e are the aspect ratios of PVA and PE fibers respectively (see Table 6); η a , η e are the bonding coefficients of PVA and PE fibers, and their values ​​are 0.25 and 0.10 respectively.

[0098] According to the fiber types and mix ratios of each group of Examples 1 to 3, the corresponding fiber influence factor λ (see Table 7) can be calculated. The influence of λ on the correction coefficients a and b is as follows: Figure 4 , Figure 5 shown.

[0099] Table 7 Fiber influence factor λ (PVA:PE) at different fiber content

[0100] serial number 1.5%:0.5% 1.25%:0.75% 1%:1% 0.75%:1.25 λ 0.116 0.112 0.109 0.106

[0101] Combining the data of Examples 1 to 3, the fiber influence factors λ and a can be obtained: λ , b λ The fitting expressions are:

[0102] a λ =33814λ 2 -8147.7λ+552.78;b λ =13504λ 2 -3044.2λ+177.49

[0103] The 28d strength prediction formula of desert sand hybrid fiber cement-based composites considering the fiber influence factor λ can be obtained:

[0104]

[0105] Based on this, the present invention carried out a group of verification tests, 500 parts of cement, 750 parts of fly ash, 445 parts of desert sand, 325 parts of water, 9.2 parts of water reducer, 9.75 parts of PVA fiber, 12.13 parts of PE fiber, 0.5 parts of thickener, Table 8 is the raw material composition information table of the verification test of Example 4, and Table 9 is the compressive strength summary table of the verification test of Example 4.

[0106] Table 8 Raw material composition information table of Example 4 verification test, unit: mass parts

[0107] serial number cement Fly ash sand water Water reducing agent PVA PE Thickener Example 4 500 750 445 325 9.2 9.75 12.13 0.5

[0108] Table 9 Example 428 days related data

[0109] serial number 28d measured value 28d predicted value Error value Example 4 56.75MPa 56.04MPa 1.25%

[0110] Example 4 Verification test fitting formula:

[0111]

[0112] In this example, the fiber influence factor λ=0.106, combined with T=28, the 28d compressive strength is obtained as shown in Table 8.

[0113] Table 9 lists the 28-day compressive strength and predicted strength of Example 4, and the prediction error is only 1.25%. It can be seen that the 28-day strength prediction method of the desert sand hybrid fiber cement-based composite material of the present invention is reasonable and has a high prediction accuracy.

[0114] In summary, the 28d strength prediction method of the desert sand hybrid fiber cement-based composite material of the present invention is feasible and effective, and can accurately and quickly predict the 28d strength of the desert sand hybrid fiber cement-based composite material, helping to shorten the detection cycle.

[0115] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0116] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for predicting the 28d strength of desert sand hybrid fiber cement-based composite materials, characterized in that: The following steps are involved: Preparation of desert sand hybrid fiber cement-based composite specimens; Curing the desert sand mixed fiber cement-based composite material specimens, and performing compressive strength tests on the cured specimens to obtain compressive strengths at different ages; The compressive strength test data of different ages are fitted with a formula to obtain a function expression between the compressive strength and the curing days, and the function expression is: Among them, T is the number of maintenance days, σ c is the compressive strength at the corresponding age, a λ , b λ is the regression coefficient considering the influence of fiber type and relative dosage, both of which are functions of fiber influence factor λ; According to the curing days and the corresponding compressive strength, the regression coefficient a considering the fiber type and relative dosage is obtained. λ and b λ , and a λ =33814λ 2 -8147.7λ+552.78, b λ =13504λ 2 -3044.2λ+177.49, substitute λ and T=28 into the fitting formula and predict the corresponding 28-day intensity.

2. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 1, characterized in that: The desert sand mixed fiber cement-based composite material comprises the following raw materials in parts by weight: 480-520 parts of cement, 730-770 parts of fly ash, 430-460 parts of desert sand, 320-330 parts of water, 9.0-9.4 parts of water reducing agent, 13-19.5 parts of polyvinyl alcohol fiber, 4.85-9.7 parts of polyethylene fiber, and 0.5 part of thickener.

3. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 1, characterized in that: a λ =62.637~66.41447, b λ =5.93775~6.11714, λ=0.106~0.

116.

4. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 1, characterized in that: The curing days are 3 to 14 days, and the curing temperature is 18° to 22°.

5. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 1, characterized in that: The curing days should be at least 2 days between the 3rd day and the 14th day.

6. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 5, characterized in that: The curing days are the 3rd, 7th and 14th days.

7. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 1, characterized in that: The error value is less than 5%.

8. The method for predicting the strength of the desert sand hybrid fiber cement-based composite material 28 according to claim 2, characterized in that: The desert sand has a mud content of 0.64% and a particle size of 74 μm to 600 μm.

9. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 2, characterized in that: The method for preparing the desert sand mixed fiber cement-based composite material specimen comprises the following steps: Weigh the following raw materials in parts by weight: 480-520 parts of cement, 730-770 parts of fly ash, 430-460 parts of desert sand, 320-330 parts of water, 9.0-9.4 parts of water reducing agent, 13-19.5 parts of polyvinyl alcohol fiber, 4.85-9.7 parts of polyethylene fiber, and 0.5 parts of thickener; Mixing 2 / 3 of the desert sand, cement and fly ash in the raw materials with water to obtain a first mixture; Adding the remaining 1 / 3 of desert sand, cement and fly ash to the first mixture, and simultaneously adding a water reducing agent, to obtain a second mixture; Subsequently, a thickener is added to the second mixture, and the mixture is stirred. Finally, polyvinyl alcohol fibers and polyethylene fibers are added and stirred to obtain a desert sand hybrid fiber cement-based composite material.

10. The method for predicting 28d strength of desert sand hybrid fiber cement-based composite material according to claim 9, characterized in that: The desert sand mixed fiber cement-based composite material was cast and then cured, and the casting size was 70.7mm×70.7mm×70.7mm.

Citation Information

Cited By

  • Steel fiber equivalent mixing analysis and evaluation method for reactive powder concrete

    CN115629197A

  • Steel fiber equivalent hybrid analysis and evaluation method for reactive powder concrete

    CN115629197B